THE ANALYSIS AND DESIGN OF LEARNING MEDIA INFORMATION TECHNOLOGY TECHNOPRENEURSHIPS BASED ON LEARNING STYLES - Novemy Triyandari Nugroho; Wiji Lestari; Rudi Susanto (Proceeding of International Conference on Science, Health, And Technology, 2022)
Technopreneurship in the field of information technology is a new entrepreneurship in the era of digitalization. Technopreneurship combines entrepreneurial skills and advances in information technology. The research analyzes and designs entrepreneurship learning media with technopreneurships content in the field of information technology. The designed learning media is expected to be used to support learning that accommodates the personal characteristics of students, especially learning styles. The analysis stages include learning styles, namely Visual, Aural, Read and Kinesthetics (VARK) learning styles, entrepreneurship learning analysis, analysis of system builder needs. The design stage consists of logical design and physical design. The physical design of the learning media will be adjusted to the student's learning style. The results of the validation of the analysis and design of this learning media from the aspects of Entrepreneurship learning content obtained 80%, software engineering aspects 93.3%, visual communication aspects 93.3% and aspects of learning design 80%.